M2M communications : a systems approach - Boswarthick, David; Elloumi, Omar; Hersent, Olivier (ETSI : Wiley, 2012)
A comprehensive introduction to M2M Standards and systems architecture, from concept to implementation Focusing on the latest technological developments, M2M Communications: A Systems Approach is an advanced introduction to this important and rapidly evolving topic. It provides a systems perspective on machine-to-machine services and the major telecommunications relevant technologies. It provides a focus on the latest standards currently in progress by ETSI and 3GPP, the leading standards entities in telecommunication networks and solutions. The structure of the book is inspired by ongoing standards developments and uses a systems-based approach for describing the problems which may be encountered when considering M2M, as well as offering proposed solutions from the latest developments in industry and standardization. The authors provide comprehensive technical information on M2M architecture, protocols and applications, especially examining M2M service architecture, access and core network optimizations, and M2M area networks technologies. It also considers dominant M2M application domains such as Smart Metering, Smart Grid, and eHealth. Aimed as an advanced introduction to this complex technical field, the book will provide an essential end-to-end overview of M2M for professionals working in the industry and advanced students. Key features: -First technical book emerging from a standards perspective to respond to this highly specific technology/business segment -Covers the main challenges facing the M2M industry today, and proposes early roll-out scenarios and potential optimization solutions -Examines the system level architecture and clearly defines the methodology and interfaces to be considered -Includes important information presented in a logical manner essential for any engineer or business manager involved in the field of M2M and Internet of Things -Provides a cross-over between vertical and horizontal M2M concepts and a possible evolution path between the two -Written by experts involved at the cutting edge of M2M developments.